PTU-118 Presenting problems and outcomes of women with gynaecological cancer attending a specialist GI symptom clinic. (8th June 2018) - Muls, Ann; Lalondrelle, Susan; Taylor, Alexandra; Norton, Christine; Hart, Ailsa; Andreyev, Jervoise
Abstract : Introduction: Worldwide 1, 470, 900 women are diagnosed yearly with a gynaecological cancer. Some women develop long-term changes in bowel function following treatment severely impacting on quality of life. Methods: A service evaluation collecting prospective data was approved by the organisation's R and D department. Intestinal symptoms were measured using a modified GSRS and impact on QoL assessed by VAS score (0=worst QoL, 10=best QoL). The McNemar Chi-square and Wilcoxon signed rank tests were used to analyse changes in symptom burden between initial assessment to discharge from the service. Results: From April 2013 to March 2016, 235 women treated for gynaecological cancers attended the clinic, representing a fifth of those using the service. Fifteen declined further intervention and were excluded, leaving 220 for analysis. Women had been treated for cancer of the cervix (50%), endometrium (28%), ovary (15%), vagina or vulva (7%) cancer. Most women received multi-modal therapies: chemoradiation (28%), surgery +radiotherapy (27%), surgery +chemoradiation (22%), surgery +chemotherapy (10%). Median age was 57 years (range: 24–83). The median time between cancer diagnosis and referral to service was 4 years and 10 months (range: 6 m–47.5 y). Most troublesome symptoms at assessment were bowel frequency of 4 or more times a day (88%), type 6 or 7 stool consistency (36%), urgency to defaecate (31%), faecal incontinence (21%) and fatigue (25%). Some women also reported urinary problems (17%) and sexual concerns (12%). Following a published algorithm, a median of 8 investigations were requested (range: 1–14): blood screen (97%), gastroscopy (75%), glucose hydrogen methane breath test (77%), SeHCAT scan (71%), faecal elastase (69%), flexible sigmoidoscopy (52%), colonoscopy (25%) and abdominal Xray (18%). A median of four factors contributing to symptoms were found (range: 1–9) and 68% of women had more than three. The most common diagnoses were vitamin D deficiency (60%), treated with replacement; SIBO (54%), treated with antibiotics and bile acid malabsorption (52%), treated with bile acid sequestrants and low fat diet. The median number of consultations was 4 (range: 1–17). Median quality of life improved from 4 at first assessment to 6 at discharge (p<0.001); the reduction in urgency, incontinence, tenesmus, frequency, diarrhoea and fatigue was statistically significant (p<0.05). Conclusions: Bowel symptoms after cancer treatment affect many women. They can be discharged with symptom improvement using a systematic investigational and treatment approach. Earlier referral to specialist services is recommended.